Magnetic behavior of transition-metal impurities in alkali-earth metals - N. Papanikolaou; N. Stefanou; R. Zeller; P.H. Dederichs (Physical Review B, 1995)
We present density-functional calculations within the local-density approximation for all transition-metal impurities in the divalent hosts Ca, Sr, and Ba. Our results predict sizable moments, even for impurities of the 4d and 5d series, being only slightly smaller than the moments obtained in the corresponding alkali metals